Unreal Engine 5 shaders and effects cookbook : over 50 recipes to help you create materials and utilize advanced shading techniques - Ramos, Brais Brenlla (Packt Publishing Ltd., 2023)
Unreal Engine is here to stay! Since the launch of the first edition of this book, based on the Unreal Engine 5 technology, real-time rendering has only grown in popularity. The demand for expertise in this area has grown exponentially across various fields over the last few years, and Unreal Engine 5 builds upon that foundation and continues to push the boundaries of what is achievable in an interactive format. Against this backdrop, the second edition of this book takes a leap forward and explores the new opportunities offered by the latest version of the engine, including Lumen, ray tracing, and Nanite. The book also revisits previously covered techniques and updates them to current standards, shining new light on topics such as the PBR workflow and the different lighting solutions that were present in the first edition. Throughout the chapters, you'll be able to focus on two key principles that you need to consider when dealing with real-time graphics: optimization and efficiency. By the end of this book, you'll have explored the many rendering possibilities that Unreal Engine 5 has to offer to become the master of your own creations!